Salivary psoriasin (S100A7) correlates with diffusion capacity of carbon monoxide in a large cohort of systemic sclerosis patients. Issue 1 (December 2016) - Giusti, Laura; Sernissi, Francesca; Donadio, Elena; Ciregia, Federica; Giacomelli, Camillo; Giannaccini, Gino; Mazzoni, Maria; Lucacchini, Antonio; Bazzichi, Laura
Abstract Background Systemic sclerosis (SSc) is an autoimmune disease characterized by progressive fibrosis of the skin and the internal organs. In a previous work we suggested a correlation between levels of salivary psoriasin (S100A7) and pulmonary involvement in SSc patients. The goals of this study are to determine the distribution characteristics of psoriasin in whole saliva (WS) of SSc and healthy donor populations and define its predictive value on diffusion capacity of carbon monoxide (DLCO), along with others clinical parameters. Methods Salivary level of psoriasin was determined by ELISA kit in 134 SSc patients, 63 Raynaud syndrome patients, 40 patients affected by other connective diseases (non-case) and 74 healthy control subjects. Results A significant increase of salivary psoriasin was observed in SSc patients when compared with other healthy and pathological controls. Moreover, we confirmed the efficacy of salivary psoriasin to correlate with DLCO in a large cohort of SSc patients. Conclusions Overall our results suggest a rapid, non invasive and low costing method which can help clinicians in the evaluation of SSc pulmonary involvement.